CHEMOTHERAPY-INDUCED THROMBOCYTOPENIA LEADING TO LIFE-THREATENING HYPOVOLEMIC SHOCK IN CERVICAL CANCER: A CASE REPORT - Nurul Fadila; Raveinal Raveinal; Fadrian Fadrian; Roza Mulyana (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2025)
Hypovolemic shock due to acute hemorrhage is a life-threatening condition, particularly in cancer patients undergoing chemotherapy. Although recent studies have established protocols for managing hypovolemic shock in trauma and sepsis, the role of chemotherapy-induced thrombocytopenia in exacerbating post-procedural bleeding risks remains underexplored. This case emphasizes the clinical complexity of managing hemorrhagic shock in advanced-stage cervical cancer patients following percutaneous nephrostomy (PCN). Case Presentation: A 52-year-old female with stage IVB cervical cancer and liver metastasis presented with hypovolemic shock following PCN. She exhibited severe hematuria and chemotherapy-induced thrombocytopenia, leading to prolonged bleeding and subsequent shock. Initial management involved aggressive fluid resuscitation, blood transfusions, and correction of thrombocytopenia. Despite the challenges of managing shock in a patient with concurrent chronic kidney disease (CKD) stage IV, prompt intervention led to significant clinical improvement, stabilization of vital signs, and eventual discharge. Conclusion: This case highlights the importance of early intervention in managing hypovolemic shock in oncology patients with multiple comorbidities, including chemotherapy-induced thrombocytopenia and CKD. A multidisciplinary approach and close monitoring are crucial for improving outcomes in such high-risk patients. Further research is needed to establish tailored management protocols for this patient population.